SISTEM PAKAR DIAGNOSIS PENYAKIT GINJAL (STUDI KASUS PADA RUMAH SAKIT ROYAL PRIMA): Symptoms, Diagnosis, Forward Chaining, Kidney Disease, Expert System - Indra, Sum; Yeniwati, Desi (JURNAL AKADEMIKA, 2019)
Along with the development of technology, the role of information technology is increasingly useful to develop in various fields including in the health sector. One of them is the system used to help diagnose kidney disease, this paper aims to design an expert system for kidney disease. In this study the method used to create a system of expert kidney disease is to use the forward chaining method. In the forward chaining method, the data search process starts from the premise to the final conclusion. This method is also called data driven, that is, the search is controlled by the data provided. The final results obtained from this study are an expert system of diagnosing kidney disease with a forward chaining method, where the user or user enters perceived symptom data according to the selection, then the results obtained in the form of symptoms, conclusions of the disease, as well as prevention advice.